The Law Enforcement Against Violations of Space Utilization in River Boundary Areas in Sintang Regency: Penegakan Hukum Terhadap Pelanggaran Pemanfaatan Ruang Kawasan Garis Sempadan Sungai Di Kabupaten Sintang - Aldi Sofiandi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
The large number of buildings scattered in the river border area in Sintang Regency indicates that there is a violation of the use of river border area space without permission in Sintang Regency. By using empirical juridical research methods, this research found that there are two regulations governing law enforcement against violations of regional space use and river borders without permits, namely the RTRW Regional Regulation and the Public Order Regional Regulation. However, these two regulations have different provisions in providing administrative sanctions and criminal sanctions against perpetrators of violations. In the RTRW Regional Regulation, criminal sanctions are not specifically mentioned but are more general for spatial planning violations, in contrast to the Public Order Regional Regulation, which more specifically mentions criminal sanctions for these violations. Furthermore, law enforcement factors include the absence of implementing regulations, information regarding the exact boundaries of river borders, and the existence of old traditional village communities that have long lived in river border areas.